Effectiveness of Schema Therapy on Symptoms of Love Trauma, Depression, and Anxiety in Young Women with Experience of Emotional Failure - Ebrahimi, Fazeleh; Amini, Naser; Keykhosrovani, Moloud (Psychology of Woman Journal, 2023)
Objective: The aim of the present study was to determine the effectiveness of schema therapy on symptoms of love trauma, depression, and anxiety in young women with experience of emotional failure.Methods and Materials: The present study employed an applied research design and a quasi-experimental pretest-posttest follow-up design with a control group. The statistical population of this study included all women aged 20-35 who visited counseling centers in the city of Amol in the year 2022. The sample of this study consisted of 40 individuals from the research community in Amol, who were selected using convenience sampling and randomly assigned to two groups: schema therapy (n=20) and control (n=20). Data were collected using the Ross Love Trauma Questionnaire (1999), the Beck Anxiety Inventory (1996), and the Beck Depression Inventory (1996). The schema therapy sessions, based on Young's (2005) approach, were held weekly over 10 sessions of 90 minutes each. Data were analyzed using repeated measures and SPSS-26 software.Findings: The results showed that schema therapy was effective on anxiety (F=18.410), depression (F=41.531), and love trauma symptoms (F=74.597) in young women with experience of emotional failure. Therefore, it can be concluded that schema therapy was effective on anxiety (F=18.410), depression (F=41.531), and love trauma symptoms (F=74.597) in young women with experience of emotional failure.Conclusion: It can be concluded that schema therapy was effective on symptoms of love trauma, depression, and anxiety in young women with experience of emotional failure.